How many acute orthopaedic injuries are preventable?. Issue 8 (August 2022) - Duggleby, Luke; Gourbault, Lysander; Parsons, Thomas; Boden, Eleanor; Barton, Tristan; Giddins, Grey
Highlights: 24% of injuries that presented to our orthopaedic department were felt to be preventable. The wrist/hand was the most frequently injured anatomical area. It also had the highest proportion of preventable injuries at 34%. Occupational injury represents a high proportion of preventable injury. Our observations build evidence that there exists a significant burden of trauma that is preventable that entails significant financial burden to the individual, healthcare system and society. Abstract: Purpose: Injury prevention is important. Injury as a result of an accident carries with it huge cost to the individual and society including health services costs. Understanding the mechanism of injury is important to identify those injuries that are preventable. The aim of this study was to assess how many acute orthopaedic injuries were preventable should reasonable human interventions have been taken Methods: This prospective study was performed in a UK district general hospital that serves a population of 500, 000 people. All patients referred to the Orthopaedic department over 4 weeks between 16th November and 14th December 2020 were reviewed. Data was collected about the mechanism of injury, patient demographics, injury type, injury location, treatment and length of stay in hospital. The mechanisms of injury were analysed thematically. Results: We assessed 605 patient attendances. 502 patients sustained 516 acute traumatic injuries. Preventable injuries were common, accounting for 23.9% of all referrals. The upper limb was most commonly injured with the hand and forearm being injured 33% of the time. Of the preventable injuries 35% were treated operatively. Thematic analysis identified common mechanisms of: occupational related, stairs, RTA, cycling, alcohol related, trampoline, DIY and assault. Conclusion: This study identifies that a large proportion of acute orthopaedic injuries are potentially preventable meaning this is an important area for further study. Occupation injuries were identified as an area in which there is the greatest scope to reduce the number of preventable accidents.